Anti-scouring coating structure of aero-engine blade disc and preparation method of anti-scouring coating structure

By adopting the Ti-TiN-Zr-ZrN multi-layer composite coating structure on the aero engine blade disc, the problems of low hardness and poor wear resistance of titanium alloy materials are solved, and higher wear resistance, corrosion resistance and hardness are achieved, which significantly improves the anti-shrink performance and service life of the blade disc.

CN119876853APending Publication Date: 2025-04-25CHINA HANGFA SOUTH IND CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411636584.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The titanium alloy material of the aircraft engine blade disc is low in hardness, poor wear resistance and poor anti-scrubbing performance of solid particles, which affects the safety and reliability and service life of the engine.

Method used

The Ti-TiN-Zr-ZrN multi-layer composite coating structure is adopted, and the Zr element is introduced through the deposition process to change the composition between the coating layers, prevent the growth of columnar crystals, refine the grains, and improve the corrosion resistance and oxidation temperature of the coating.

Benefits of technology

It significantly improves the wear resistance, corrosion resistance and hardness of the coating, enhances the anti-shrink performance of solid particles, extends the service life of the blade disc and improves reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876853A_ABST
    Figure CN119876853A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-scouring coating structure for a blade disc of an aero-engine and a preparation method of the anti-scouring coating structure. The coating structure comprises a transition layer combined with a base body and a plurality of repeated-period alternating layers combined with the transition layer. The alternating layer structure sequentially comprises a Ti metal layer, a TiN ceramic layer, a Zr metal layer and a ZrN ceramic layer from a base body to the surface, and the number n of times of the repetition period is larger than or equal to 3. In addition, the invention further discloses a preparation method of the coating structure, and the preparation method comprises the steps that S1, a cleaned workpiece is installed on a clamp and hung into a coating chamber; and S2, starting and stopping of the Ti target and the Zr target and the types of introduced gas are adjusted through the PVD coating technology, and a transition layer and an alternating layer are sequentially deposited. According to the preparation method, columnar crystals in the film layer are effectively prevented from being increased, crystal grains are finer, and the ZrN film has better corrosion resistance and higher oxidation resistance temperature than a TiN film, so that the wear resistance, corrosion resistance and hardness of the coating are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coating materials, and more specifically, to an anti-scouring coating structure of an aircraft engine blade disk and a preparation method thereof. Background Art

[0002] Scour wear refers to the erosion of solid particles caused by solid particles being entrained by airflow and hitting the surface of components. It is a common wear phenomenon in engineering materials, especially high-speed rotating components such as aircraft engines. It is generally believed that when the flight speed reaches 300m / s, solid particles such as dust and sand in the air will inevitably be sucked into the turbine engine under the action of high-speed airflow, impacting and wearing the blades, especially large particles with a diameter greater than 30μm can even deform the blades, affecting the engine performance or causing it to fail. The titanium alloy integral blade disk of a certain model of engine is an important component of the engine compressor. Due to the comprehensive properties of titanium alloy materials with high specific strength and high specific stiffness, excellent corrosion resistance and good high-temperature mechanical properties, aircraft engines mostly use axial flow blade disks made of titanium alloy substrates. However, titanium alloy has low hardness and poor wear resistance, so its anti-scouring performance against solid particles is poor, which greatly affects the safety and reliability of aircraft engines. Therefore, in order to make the engine adapt to the harsh use environment, it is necessary to develop an anti-scour coating on the surface of the titanium alloy integral blade disk to extend its service life and improve its reliability.

[0003] Invention patent CN107326361B discloses a gradient multilayer composite coating structure with high resistance to sand and dust erosion. The coating structure integrates ion implantation structure, gradient structure and multilayer structure. From the substrate to the coating surface, it contains an ion implantation bonding layer and a structure composed of a Ti metal layer, a Ti→TiN gradient layer, a TiN ceramic layer and a TiN→Ti gradient layer cyclically superimposed. The TiN layer in the multilayer composite coating structure has poor oxidation resistance, and its life will be greatly reduced under high temperature conditions for a long time; the interlayer composition of the multilayer coating in the coating structure is close, and the grain growth particles are larger, thereby reducing the wear resistance, corrosion resistance and hardness of the coating. Summary of the invention

[0004] In order to solve the above technical problems, the present invention introduces the Zr element, which has a deposition process similar to that of the Ti element, to achieve the change of the interlayer composition of the multilayer coating, more effectively prevent the growth of columnar crystals in the film layer, and thus refine the grains. At the same time, the ZrN film has better corrosion resistance and higher oxidation resistance temperature than the TiN film. An anti-scour coating structure for an aircraft engine blade disk and a preparation method thereof are proposed.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] An anti-scour coating structure for an aircraft engine blade disk, the coating structure comprising a transition layer combined with a substrate and a plurality of repeated periodic alternating layers combined with the transition layer; the alternating layer structure is a Ti metal layer, a TiN ceramic layer, a Zr metal layer, and a ZrN ceramic layer in sequence; the number of the period n is ≥3.

[0007] Furthermore, the transition layer is a TiN ceramic layer.

[0008] Furthermore, the ratio of the total thickness of the Ti metal layer and the TiN ceramic layer to the total thickness of the Zr metal layer and the ZrN ceramic layer is 1:0.5-2, the ratio of the Ti metal layer thickness to the TiN ceramic layer metal layer thickness is 1:1-6, and the ratio of the Zr metal layer thickness to the ZrN ceramic layer metal layer thickness is 1:1-6.

[0009] Furthermore, the coating film thickness of each period is 0.2-2 μm.

[0010] Preferably, the number of cycles n≥24.

[0011] A method for preparing an anti-scouring coating structure of an aircraft engine blade disk comprises the following steps:

[0012] S1: Place the cleaned workpiece on the fixture and hang it in the coating chamber;

[0013] S2: PVD coating deposits multiple alternating layers:

[0014] Depositing Ti metal layer: heating to 200-400°C, introducing 0.1-0.5 Pa of argon, setting the bias voltage to 100-200 V, turning on the Ti target, the arc current to 60 A-90 A, and the cleaning time to 1-4 min;

[0015] Deposition of TiN layer: heating to 200-400°C, introducing a mixture of argon and nitrogen at 0.1-0.5 Pa, setting the bias voltage to 100-200 V, turning on the Ti target, the arc current to 60-90 A, and the cleaning time to 3-8 min;

[0016] Depositing Zr layer: heating to 200-400°C, introducing 0.1-0.5 Pa of argon, setting the bias voltage to 100-200 V, turning on the Zr target, the arc current to 80-110 A, and the cleaning time to 0.5-2.5 min;

[0017] Deposition of ZrN layer: heat to 200-400°C, introduce 0.1-0.5Pa of argon and nitrogen mixture, set the bias voltage to 100-200V, turn on the Zr target, the arc current is 80-110A, and the cleaning time is 1-4min.

[0018] Furthermore, the S1 cleaning includes wet sandblasting pre-treatment, rough cleaning with cleaning fluid, fine cleaning with cleaning fluid, deionized water cleaning and dehydration treatment.

[0019] Furthermore, before the coating step S2, the sample surface is cleaned by argon ion glow for 40 to 60 minutes using a bias discharge of -550V to -850V.

[0020] Furthermore, the number of the multiple alternating layers in step S2 is ≥3.

[0021] Furthermore, the clamp is a tubular structure, including a base and a mounting plate, the base is adapted to the diameter of the blade disk mounting shaft, and the mounting plate is fixedly connected to the base by bolts to fix the blade disk.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1) The present invention introduces a Zr metal layer and a ZrN ceramic layer to form a multilayer composite coating of a Ti metal layer, a TiN ceramic layer, a Zr metal layer, and a ZrN ceramic layer, which effectively prevents the growth of columnar crystals in the film layer and makes the grains finer. In addition, the ZrN film has better corrosion resistance and higher oxidation resistance temperature than the TiN film, thereby improving the wear resistance, corrosion resistance and hardness of the coating.

[0024] 2) The present invention realizes the protection of the non-coated surface and avoids the problem of uneven film thickness caused by the complex structure of the blade by designing a clamping fixture for furnace loading. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic diagram of the structure of the anti-scour coating of the present invention;

[0026] Figure 2 Surface and cross-sectional morphology of the coating in Examples 1 to 3;

[0027] Figure 3 Surface and cross-sectional morphology of the coating in Examples 4 to 6;

[0028] Figure 4 Surface and cross-sectional morphology of the coating in Examples 7 to 9;

[0029] Figure 5 The scratch morphology of the coating adhesion in Examples 1 to 9;

[0030] Figure 6 This is a schematic diagram of a fixture structure for clamping blades of an aircraft engine;

[0031] Figure 7 A schematic diagram of the clamping of an aircraft engine blade disk;

[0032] Including: 1. Base; 2. Mounting plate. DETAILED DESCRIPTION

[0033] The following is further explained and illustrated in conjunction with the examples, but the specific examples do not limit the present invention in any form. If not specifically stated, the methods and equipment used in the examples are conventional methods and equipment in the art, and the raw materials used are all conventional commercially available raw materials.

[0034] The present invention provides an anti-scour coating structure for an aircraft engine blade disk, the coating structure comprising a transition layer combined with a substrate and a plurality of repeated periodic alternating layers combined with the transition layer; the alternating layer structure is a Ti metal layer, a TiN ceramic layer, a Zr metal layer and a ZrN ceramic layer in sequence from the substrate to the surface; the number of the cycles is ≥3.

[0035] The present invention deposits a transition layer that is well bonded to the substrate material to ensure that the multilayer coating is firmly bonded to the substrate; then deposits four layers of Ti, TiN, Zr, and ZrN in sequence as a cycle, and repeats multiple cycles according to experimental needs. This design is mainly based on the fact that the metal nitride (MeN) ceramic film has high hardness, good wear resistance and corrosion resistance, but is brittle and has poor impact resistance; therefore, inserting a metal (Me) soft layer into the metal nitride (MeN) ceramic film can improve the toughness of the film layer and reduce the internal stress of the film layer by adjusting the proportion of the metal soft layer. The use of TiN-based anti-erosion and wear film layer is a successful example of existing applications abroad, and the low cost of Ti target material is conducive to engineering production; the introduction of Zr elements, which have a deposition process similar to that of Ti elements, can mainly achieve changes in the interlayer composition of the multilayer coating, more effectively prevent the growth of columnar crystals in the film layer and refine the grains. At the same time, the ZrN film has better corrosion resistance and higher oxidation resistance temperature than the TiN film.

[0036] The structure of the Ti-TiN-Zr-ZrN multilayer coating was optimized by orthogonal experiment. Under the condition that the film thickness is at the same level, the design cycle number, the metal to metal nitride thickness ratio (RMe:RMeN) and the titanium base to zirconium base thickness ratio (RTi / TiN:RZr / ZrN) are the influencing factors. The experiment adopts the orthogonal test method of three factors and three levels, and the parameters are shown in Table 1; according to the four factors and three levels, the orthogonal experiment is set to set 9 groups of embodiments, and the parameter settings of the embodiments are shown in Table 2.

[0037] Table 1. Level table of factors in orthogonal test of coating structure

[0038] level (A) Number of cycles (B)RMe:RMeN (C)RTi / TiN:RZr / ZrN 1 3 1:6 1:2 2 12 1:3 1:1 3 24 1:1 2:1

[0039] Table 2 Orthogonal design of coating structure parameters

[0040] Example Number of cycles RMe:RMeN RTi / TiN:RZr / ZrN Example 1 3 1:6 1:2 Example 2 3 1:3 1:1 Example 3 3 1:1 1:0.5 Example 4 12 1:6 1:1 Example 5 12 1:3 1:0.5 Example 6 12 1:1 1:2 Example 7 24 1:6 1:0.5 Example 8 24 1:3 1:2 Example 9 24 1:1 1:1

[0041] Example 1

[0042] As shown in Table 2, this embodiment provides an anti-scour coating structure for an aircraft engine blade disk.

[0043] The coating structure includes a transition layer combined with a substrate and a plurality of repeated alternating layers combined with the transition layer; the alternating layer structure is Ti metal layer, TiN ceramic layer, Zr metal layer and ZrN ceramic layer in sequence from the substrate to the surface; the number of repeated cycles is 3.

[0044] The transition layer is a TiN ceramic layer.

[0045] The ratio of the total thickness of the Ti metal layer and the TiN ceramic layer to the total thickness of the Zr metal layer and the ZrN ceramic layer is 1:2, the ratio of the Ti metal layer thickness to the TiN ceramic layer metal layer thickness is 1:6, and the ratio of the Zr metal layer thickness to the ZrN ceramic layer metal layer thickness is 1:6.

[0046] Example 2

[0047] As shown in Table 2, this embodiment provides an anti-scour coating structure for an aircraft engine blade disk.

[0048] The coating structure includes a transition layer combined with a substrate and a plurality of repeated alternating layers combined with the transition layer; the alternating layer structure is Ti metal layer, TiN ceramic layer, Zr metal layer and ZrN ceramic layer in sequence from the substrate to the surface; the number of repeated cycles is 3.

[0049] The transition layer is a TiN ceramic layer.

[0050] The ratio of the total thickness of the Ti metal layer and the TiN ceramic layer to the total thickness of the Zr metal layer and the ZrN ceramic layer is 1:1, the ratio of the Ti metal layer thickness to the TiN ceramic layer metal layer thickness is 1:3, and the ratio of the Zr metal layer thickness to the ZrN ceramic layer metal layer thickness is 1:3.

[0051] Example 3

[0052] As shown in Table 2, this embodiment provides an anti-scour coating structure for an aircraft engine blade disk.

[0053] The coating structure includes a transition layer combined with a substrate and a plurality of repeated alternating layers combined with the transition layer; the alternating layer structure is Ti metal layer, TiN ceramic layer, Zr metal layer and ZrN ceramic layer in sequence from the substrate to the surface; the number of repeated cycles is 3.

[0054] The transition layer is a TiN ceramic layer.

[0055] The ratio of the total thickness of the Ti metal layer and the TiN ceramic layer to the total thickness of the Zr metal layer and the ZrN ceramic layer is 1:0.5, the ratio of the Ti metal layer thickness to the TiN ceramic layer metal layer thickness is 1:1, and the ratio of the Zr metal layer thickness to the ZrN ceramic layer metal layer thickness is 1:1.

[0056] Example 4

[0057] As shown in Table 2, this embodiment provides an anti-scour coating structure for an aircraft engine blade disk.

[0058] The coating structure includes a transition layer combined with a substrate and a plurality of repeated periodic alternating layers combined with the transition layer; the alternating layer structure is Ti metal layer, TiN ceramic layer, Zr metal layer and ZrN ceramic layer in sequence from the substrate to the surface; the number of repeated periods is 12.

[0059] The transition layer is a TiN ceramic layer.

[0060] The ratio of the total thickness of the Ti metal layer and the TiN ceramic layer to the total thickness of the Zr metal layer and the ZrN ceramic layer is 1:1, the ratio of the Ti metal layer thickness to the TiN ceramic layer metal layer thickness is 1:6, and the ratio of the Zr metal layer thickness to the ZrN ceramic layer metal layer thickness is 1:6.

[0061] Example 5

[0062] As shown in Table 2, this embodiment provides an anti-scour coating structure for an aircraft engine blade disk.

[0063] The coating structure includes a transition layer combined with a substrate and a plurality of repeated periodic alternating layers combined with the transition layer; the alternating layer structure is Ti metal layer, TiN ceramic layer, Zr metal layer and ZrN ceramic layer in sequence from the substrate to the surface; the number of repeated periods is 12.

[0064] The transition layer is a TiN ceramic layer.

[0065] The ratio of the total thickness of the Ti metal layer and the TiN ceramic layer to the total thickness of the Zr metal layer and the ZrN ceramic layer is 1:0.5, the ratio of the Ti metal layer thickness to the TiN ceramic layer metal layer thickness is 1:3, and the ratio of the Zr metal layer thickness to the ZrN ceramic layer metal layer thickness is 1:3.

[0066] Example 6

[0067] As shown in Table 2, this embodiment provides an anti-scour coating structure for an aircraft engine blade disk.

[0068] The coating structure includes a transition layer combined with a substrate and a plurality of repeated periodic alternating layers combined with the transition layer; the alternating layer structure is Ti metal layer, TiN ceramic layer, Zr metal layer and ZrN ceramic layer in sequence from the substrate to the surface; the number of repeated periods is 12.

[0069] The transition layer is a TiN ceramic layer.

[0070] The ratio of the total thickness of the Ti metal layer and the TiN ceramic layer to the total thickness of the Zr metal layer and the ZrN ceramic layer is 1:2, the ratio of the Ti metal layer thickness to the TiN ceramic layer metal layer thickness is 1:1, and the ratio of the Zr metal layer thickness to the ZrN ceramic layer metal layer thickness is 1:1.

[0071] Example 7

[0072] As shown in Table 2, this embodiment provides an anti-scour coating structure for an aircraft engine blade disk.

[0073] The coating structure includes a transition layer combined with a substrate and a plurality of repeated periodic alternating layers combined with the transition layer; the alternating layer structure is Ti metal layer, TiN ceramic layer, Zr metal layer and ZrN ceramic layer in sequence from the substrate to the surface; the number of repeated periods is 24.

[0074] The transition layer is a TiN ceramic layer.

[0075] The ratio of the total thickness of the Ti metal layer and the TiN ceramic layer to the total thickness of the Zr metal layer and the ZrN ceramic layer is 1:0.5, the ratio of the Ti metal layer thickness to the TiN ceramic layer metal layer thickness is 1:6, and the ratio of the Zr metal layer thickness to the ZrN ceramic layer metal layer thickness is 1:6.

[0076] Example 8

[0077] As shown in Table 2, this embodiment provides an anti-scour coating structure for an aircraft engine blade disk.

[0078] The coating structure includes a transition layer combined with a substrate and a plurality of repeated periodic alternating layers combined with the transition layer; the alternating layer structure is Ti metal layer, TiN ceramic layer, Zr metal layer and ZrN ceramic layer in sequence from the substrate to the surface; the number of repeated periods is 24.

[0079] The transition layer is a TiN ceramic layer.

[0080] The ratio of the total thickness of the Ti metal layer and the TiN ceramic layer to the total thickness of the Zr metal layer and the ZrN ceramic layer is 1:2, the ratio of the Ti metal layer thickness to the TiN ceramic layer metal layer thickness is 1:3, and the ratio of the Zr metal layer thickness to the ZrN ceramic layer metal layer thickness is 1:3.

[0081] Example 9

[0082] As shown in Table 2, this embodiment provides an anti-scour coating structure for an aircraft engine blade disk.

[0083] The coating structure includes a transition layer combined with a substrate and a plurality of repeated periodic alternating layers combined with the transition layer; the alternating layer structure is Ti metal layer, TiN ceramic layer, Zr metal layer and ZrN ceramic layer in sequence from the substrate to the surface; the number of repeated periods is 24.

[0084] The transition layer is a TiN ceramic layer.

[0085] The ratio of the total thickness of the Ti metal layer and the TiN ceramic layer to the total thickness of the Zr metal layer and the ZrN ceramic layer is 1:1, the ratio of the Ti metal layer thickness to the TiN ceramic layer metal layer thickness is 1:1, and the ratio of the Zr metal layer thickness to the ZrN ceramic layer metal layer thickness is 1:1.

[0086] Analyze the coating based on the test results:

[0087] 1) Comparative analysis of morphology and structure

[0088] Figure 2 The surface and cross-sectional morphology of the Ti-TiN-Zr-ZrN multilayer coating with three cycles in Examples 1 to 3 in the orthogonal test. The darker part in the figure is the Ti-TiN layer, the lighter part is the Zr-ZrN layer, and there is a thicker TiN transition layer at the interface with the substrate. Figure 2 It can be seen that there are many particles on the surface of the 3-cycle multilayer coating, and the particles almost cover the entire surface, making the surface rough. Figure 2 a2 is the cross-sectional morphology of the multilayer coating of Example 1, with a total of 3 periods. After measurement, the total thickness of the multilayer coating is about 8.0 μm, the transition layer is about 1.7 μm, and each period is about 2.1 μm (wherein the Ti-TiN layer is about 0.6 μm, the Zr-ZrN layer is about 1.5 μm, and the RTi / TiN:RZr / ZrN is actually about 1:2.5); Figure 2 b2 is the cross-sectional morphology of the multilayer coating of Example 2, which also has 3 periods. The thickness of each period is about 2.0 μm (the Ti-TiN layer is about 0.9 μm, the Zr-ZrN layer is about 1.1 μm, and the actual RTi / TiN:RZr / ZrN is about 1:1.2), the transition layer thickness is about 1.5 μm, and the total thickness of the multilayer coating is about 7.5 μm. Figure 2In c2, the cross-sectional morphology of the multilayer coating of Example 3 is shown, with a total of 3 cycles, and the thickness of each cycle is about 2.1 μm (of which the Ti-TiN layer is about 1.4 μm, the Zr-ZrN layer is about 0.7 μm, and the RTi / TiN:RZr / ZrN is actually about 2:1), the thickness of the transition layer is about 2.3 μm, and the total thickness of the multilayer coating is about 8.6 μm. In summary, the total thickness of the prepared 3-cycle Ti-TiN-Zr-ZrN multilayer coating is in the range of 7 to 9 μm, the thickness of each cycle is about 2 μm, and the RTi / TiN:RZr / ZrN thickness ratio is basically consistent with the design, the surface quality is average, and there are many particles.

[0089] Figure 3 The surface and cross-sectional morphology of the Ti-TiN-Zr-ZrN multilayer coating with 12 cycles in Examples 4 to 6 in the orthogonal test. Similarly, the dark part is the Ti-TiN layer, the light part is the Zr-ZrN layer, and there is a TiN transition layer at the interface with the substrate. Figure 3 It can be seen that there are still many particles on the surface of the 12-cycle multi-layer coating, but compared with the surface of the 3-cycle multi-layer coating, the particles are obviously reduced a lot, and the surface quality is better than that of the 3-cycle multi-layer coating. Figure 3 In d2, the cross-sectional morphology of the multilayer coating of Example 4 is shown. There are 12 periods in total. After measurement, the thickness of each period is about 0.57 μm (including the Ti-TiN layer of about 0.27 μm, the Zr-ZrN layer of about 0.30 μm, and the actual RTi / TiN:RZr / ZrN of about 1:1.1), the thickness of the transition layer is about 1.6 μm, and the total thickness of the multilayer coating is about 8.4 μm. Figure 3 In figure e2, the cross-sectional morphology of the multilayer coating of Example 5 is shown, with a total of 12 periods. The thickness of each period is about 0.44 μm (the Ti-TiN layer is about 0.22 μm, the Zr-ZrN layer is about 0.22 μm, and the actual RTi / TiN:RZr / ZrN is about 1:1). The thickness of the transition layer is about 1.2 μm, and the total thickness of the multilayer coating is about 6.5 μm. Figure 3 f2 is the cross-sectional morphology of the multilayer coating of Example 6, with a total of 12 cycles, each cycle thickness of about 0.50 μm (of which the Ti-TiN layer is about 0.12 μm, the Zr-ZrN layer is about 0.38 μm, and the RTi / TiN:RZr / ZrN is actually about 1:3.1), the transition layer thickness is about 1.4 μm, and the total thickness of the multilayer coating is about 7.4 μm. In summary, the total thickness of the prepared 12-cycle Ti-TiN-Zr-ZrN multilayer coating is in the range of 6 to 9 μm, the thickness of each cycle is about 0.5 μm, the surface quality is significantly improved compared with 3 cycles, and the particles are reduced.

[0090] Figure 4The surface and cross-sectional morphology of the Ti-TiN-Zr-ZrN multilayer coating with 24 cycles in the orthogonal test of Examples 7 to 9. It can be seen from the figure that the surface particles of the 24-cycle multilayer coating are greatly reduced, and the surface quality is better than that of the 3-cycle and 12-cycle multilayer coatings. Figure 4 Figure g2 is the cross-sectional morphology of the multilayer coating of Example 7, which has a total of 24 periods. After measurement, the thickness of each period is about 0.30 μm (including the Ti-TiN layer of about 0.17 μm, the Zr-ZrN layer of about 0.13 μm, and the actual RTi / TiN:RZr / ZrN of about 1.3:1), the transition layer thickness is about 1.3 μm, and the total thickness of the multilayer coating is about 8.5 μm. Figure 4 h2 is the cross-sectional morphology of the multilayer coating of Example 8, with a total of 24 periods, each period having a thickness of approximately 0.29 μm (of which the Ti-TiN layer is approximately 0.09 μm, the Zr-ZrN layer is approximately 0.20 μm, and the actual RTi / TiN:RZr / ZrN is approximately 1:2.2), the transition layer thickness is approximately 1.1 μm, and the total thickness of the multilayer coating is approximately 8.1 μm. Figure 4 i2 is the cross-sectional morphology of the multilayer coating of Example 9, with a total of 24 cycles, and the thickness of each cycle is about 0.27μm (wherein the Ti-TiN layer is about 0.12μm, the Zr-ZrN layer is about 0.15μm, and the actual RTi / TiN:RZr / ZrN is about 1:1.3), the thickness of the transition layer is about 1.0μm, and the total thickness of the multilayer coating is about 7.5μm. In summary, the total thickness of the prepared 24-cycle Ti-TiN-Zr-ZrN multilayer coating is in the range of 7 to 9μm, the thickness of each cycle is about 0.3μm, and the surface quality is significantly better than that of 3 and 12 cycles.

[0091] 2) Hardness comparison analysis

[0092] The microhardness test results of Ti-TiN-Zr-ZrN multilayer coating and TiN and ZrN single layer films are shown in Table 3.

[0093] Table 3 Microhardness test results of coating

[0094] Sample No. Number of cycles Hardness average value (HV) TiN / 2014 ZGar / 2258 Example 1 3 2671 Example 2 3 2510 Example 3 3 2430 Example 4 12 2998 Example 5 12 2901 Example 6 12 2851 Example 7 24 3328 Example 8 24 3102 Example 9 24 2998

[0095] As shown in Table 3, the Vickers microhardness of the 3-cycle multilayer coating is (2430-2671) Hv, the hardness of the 12-cycle multilayer coating is (2851-2998) Hv, and the hardness of the 24-cycle multilayer coating is (2998-3328) Hv. Under the same process parameters, the hardness of the single-layer TiN film deposited is 2014 Hv, and the hardness of the ZrN film is 2258 Hv. From the hardness comparison, it can be seen that the hardness of the multilayer coating is significantly higher than that of the single-layer TiN film and ZrN film, and it is shown that the hardness of the multilayer coating increases significantly with the increase of the number of cycles. This is mainly due to the increase in the number of cycles, which makes the interlayer interfaces in the multilayer coating increase exponentially, and the film layer repeatedly nucleates between the interlayer interfaces during the growth process, so that the deposited film layer has fine grains and high density.

[0096] 3) Analysis of coating adhesion

[0097] Figure 5 It is the scratch morphology of the multilayer coating sample of Examples 1 to 9 in the orthogonal test. It can be seen from the figure that for the 3-cycle multilayer coating, the bonding force is basically at the level of about 30N, the bonding force of the 12-cycle multilayer coating is at the level of about 40N, and the bonding force of the 24-cycle multilayer coating is at the level of about 60N. Under the condition of equal total thickness of the multilayer coating at different cycles, the film / substrate bonding force increases with the increase of the number of cycles. The main reason is basically the same as the reason for the increase in hardness. It is also because with the increase in the number of cycles, the number of metal "droplets" decreases and the size becomes smaller, which means that there are fewer "defects" in the film layer, and the density and flatness of the film layer are improved, which are conducive to the improvement of the cohesion of the film layer and the film / substrate bonding strength, thereby reflecting a higher film / substrate bonding force.

[0098] 4) Analysis of sand erosion and wear resistance

[0099] During the process optimization test phase of the Ti-TiN-Zr-ZrN multilayer coating, sand erosion and wear tests were carried out at 30° erosion angle and 90° erosion angle, respectively, and the amount of sand eroded to the multilayer coating to be damaged was used to evaluate its ability to resist sand erosion and wear. Table 4 lists the amount of sand erosion and wear resistance of the multilayer coatings prepared in Examples 1 to 9 at 30° erosion angle and 90° erosion angle, respectively.

[0100] Table 4 Test results of coating's ability to resist sand erosion

[0101] Test No. 30° anti-scouring sand quantity / g 90° anti-scouring sand quantity / g Example 1 20.0 4.0 Example 2 19.3 5.4 Example 3 21.0 7.0 Example 4 21.0 6.0 Example 5 20.0 5.5 Example 6 21.0 8.0 Example 7 22.0 9.0 Example 8 24.5 8.0 Example 9 23.7 8.5

[0102] From the data in the analysis table, it can be seen that with the increase of the number of cycles, the resistance of the multilayer coating to sand erosion and wear is gradually improving. This is mainly because the hardness, bonding strength and flatness of the film layer are improved with the increase of the number of cycles, and the defects in the film layer are reduced; at the same time, during the sand erosion process, the metal soft layer in the multilayer coating can effectively buffer the expansion of the brittle cracks in the ceramic layer. The more interlayer interfaces there are, the more times the buffering is, and the slower the crack expansion speed is, thus reflecting better erosion and wear resistance.

[0103] Test results analysis

[0104] The hardness, bonding strength and erosion resistance of the Ti-TiN-Zr-ZrN multilayer film were evaluated by orthogonal test. The results are shown in Table 5.

[0105] Table 5 Orthogonal test results

[0106]

[0107] According to the analysis method of single index of orthogonal test, each index is analyzed visually first, and the primary and secondary relationship and optimal solution of each factor are obtained, as shown in Table 6 Orthogonal test result analysis. In the table, Ki represents the sum of the test results corresponding to level number i (in this test i = 1, 2, 3), and ki is its average value. The R range is the difference between the maximum and minimum values ​​in ki.

[0108] Table 6 Analysis of orthogonal test results

[0109]

[0110]

[0111] The four standard optimization schemes are only the optimal schemes for the corresponding test indicators. They are independent of each other and have little applicability to each other. In order to obtain an optimization scheme suitable for the four test indicators, it is necessary to conduct a comprehensive balance analysis of various factors, as follows:

[0112] ① The influence of the number of cycles (A) on each index: It can be seen from Table 6 that for the four test indexes, the range of the number of cycles (A) is the largest, that is, the number of cycles (A) is the most influential factor, and the best level is A3.

[0113] ② The influence of the thickness ratio of metal to metal nitride RMe:RMeN(B) on each test index: It can be seen from Table 6 that although the B3 level is the best for 30° and 90° erosion resistance and bonding strength, the gap with B1 and B2 is small, and the hardness is best at the B1 level. Combined with the surface particle situation, the B1 process parameters are finally adopted.

[0114] ③ The influence of the thickness ratio of titanium base to zirconium base RTi / TiN:RZr / ZrN (C) on various indicators: From Table 6, it can be seen that C3 is superior in terms of hardness, bonding strength and 90° erosion resistance, while C1 is better in terms of 30° erosion resistance. Comprehensive evaluation, C3 process parameters are adopted.

[0115] In summary, the preferred structure of the preparation process of Ti-TiN-Zr-ZrN multilayer film is 200-300nm per period, the thickness ratio of metal to metal nitride RMe:RMeN=1:6, and the thickness ratio of titanium base to zirconium base RTi / TiN:RZr / ZrN=1:0.5.

[0116] Example 10

[0117] The present embodiment provides a method for preparing an anti-scour coating structure of an aircraft engine blade disk. The coating structure is a preferred process structure of the present invention. The coating structure includes a transition layer TiN combined with a substrate and a plurality of repeated alternating layers combined with the transition layer; the alternating layer structure is Ti metal layer, TiN ceramic layer, Zr metal layer, and ZrN ceramic layer from the substrate to the surface; the number n of the cycles is 24.

[0118] The ratio of the total thickness of the Ti metal layer and the TiN ceramic layer to the total thickness of the Zr metal layer and the ZrN ceramic layer is 1:0.5, the ratio of the Ti metal layer thickness to the TiN ceramic layer metal layer thickness is 1:6, and the ratio of the Zr metal layer thickness to the ZrN ceramic layer metal layer thickness is 1:6.

[0119] Before coating, the axial flow blade disk is cleaned, including wet sandblasting pre-treatment, rough cleaning with cleaning fluid, fine cleaning with cleaning fluid, deionized water cleaning and dehydration. Then the sample that meets the cleaning quality requirements is hoisted on the fixture.

[0120] As attached Figure 6 , Attachment Figure 7 As shown, the clamp is a tubular structure, including a base 1 and a mounting plate 2. The base 1 is adapted to the diameter of the blade disk mounting shaft. The blade is inserted into the base 1, and then the mounting plate 1 and the base 2 are locked by bolts to fix the blade disk on the clamp.

[0121] Using the PVD coating process, the blade disk mounted on a fixture is hung into the coating chamber and multiple alternating layers are deposited in sequence:

[0122] Deposition of Ti metal layer: heating to 300°C, passing 0.3Pa of argon, setting the bias voltage to 150V, turning on the Ti target, the arc current to 80A, and the cleaning time to 3min;

[0123] Deposition of TiN layer: heating to 300°C, introducing a mixture of argon and nitrogen at 0.3 Pa, setting the bias voltage to 150 V, turning on the Ti target, the arc current to 80 A, and the cleaning time to 5 min;

[0124] Deposition of Zr layer: heating to 300°C, passing 0.3Pa of argon, setting the bias voltage to 150V, turning on the Zr target, the arc current to 100A, and the cleaning time to 1.5min;

[0125] Deposition of ZrN layer: heat to 300°C, pass 0.3Pa of argon and nitrogen mixture, set the bias voltage to 150V, turn on the Zr target, the arc current is 100A, and the cleaning time is 2min.

[0126] The number of multiple alternating layers is 24.

[0127] The coated test piece was dissected and the thickness distribution of different parts was analyzed. The test results showed that the coating at the edge of the blade was the thickest (about 20μm). This was because the blade was flat and the edge was too thin, resulting in an edge effect, which led to a thicker coating thickness during the coating deposition process. The coating thickness on the blade surface was about 10μm, which was in line with the coating process design, and the outer thickness value was higher than the inner thickness value. This was because the interval between the blades of the axial flow blade disk was small, and there was a certain shielding effect, which was blocked during the deposition on the inner side, resulting in a thinner thickness. The coating thickness at the root of the axial flow blade disk was the thinnest, about 5μm. This was because the root was farthest from the target material and the shielding effect was the most serious, so the thickness was the thinnest. At the same time, during the operation of the axial flow blade disk, due to the shielding effect, the root was the least eroded by sand particles, and was mainly a load-bearing part. Therefore, only a thinner anti-erosion coating needed to be deposited to ensure that the mechanical properties of the root were not affected, thereby meeting its service requirements.

[0128] The anti-scouring coating structure of the aircraft engine blade disk prepared by the above preparation method has a coating thickness on the blade disk surface ranging from 10 to 30 μm, and the coating hardness can reach 2000 to 2500 Hv. After being coated with the anti-scouring coating, the anti-scouring performance of the axial flow blade disk is improved by 3 to 5 times compared with the uncoated specimen.

[0129] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. An anti-scouring coating structure for an aircraft engine blade disk, characterized in that: The coating structure comprises a transition layer combined with a substrate and a plurality of repeated periodic alternating layers combined with the transition layer; the alternating layer structure is Ti metal layer, TiN ceramic layer, Zr metal layer and ZrN ceramic layer in sequence; the number of the period n≥3.

2. The anti-scouring coating structure of an aircraft engine blade disk according to claim 1, characterized in that: The transition layer is a TiN ceramic layer.

3. The anti-scouring coating structure of an aircraft engine blade disk according to claim 1, characterized in that: The ratio of the total thickness of the Ti metal layer and the TiN ceramic layer to the total thickness of the Zr metal layer and the ZrN ceramic layer is 1:0.5-2, the ratio of the Ti metal layer thickness to the TiN ceramic layer metal layer thickness is 1:1-6, and the ratio of the Zr metal layer thickness to the ZrN ceramic layer metal layer thickness is 1:1-6.

4. The anti-scouring coating structure of an aircraft engine blade disk according to claim 1, characterized in that: The coating film thickness of each period is 0.2-2 μm.

5. The anti-scouring coating structure of an aircraft engine blade disk according to claim 1, characterized in that: The preferred value of the number of cycles n is n≥24.

6. A method for preparing the anti-scouring coating structure of an aircraft engine blade disk according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: Place the cleaned workpiece on the fixture and hang it in the coating chamber; S2: PVD coating deposits multiple alternating layers: Depositing Ti metal layer: heating to 200-400°C, introducing 0.1-0.5 Pa of argon, setting the bias voltage to 100-200 V, turning on the Ti target, the arc current to 60-90 A, and the cleaning time to 1-4 min; Deposition of TiN layer: heating to 200-400°C, introducing a mixture of argon and nitrogen at 0.1-0.5 Pa, setting the bias voltage to 100-200 V, turning on the Ti target, the arc current to 60-90 A, and the cleaning time to 3-8 min; Depositing Zr layer: heating to 200-400°C, introducing 0.1-0.5 Pa of argon, setting the bias voltage to 100-200 V, turning on the Zr target, the arc current to 80-110 A, and the cleaning time to 0.5-2.5 min; Deposition of ZrN layer: heat to 200-400°C, introduce 0.1-0.5Pa of argon and nitrogen mixture, set the bias voltage to 100-200V, turn on the Zr target, the arc current is 80-110A, and the cleaning time is 1-4min.

7. The method for preparing an anti-scouring coating structure for an aircraft engine blade disk according to claim 6, characterized in that: The S1 cleaning includes wet sandblasting pre-treatment, rough cleaning with cleaning solution, fine cleaning with cleaning solution, deionized water cleaning and dehydration treatment.

8. The method for preparing an anti-scouring coating structure for an aircraft engine blade disk according to claim 6, characterized in that: The step S2 also includes using a bias discharge of -550V to -850V to perform argon ion glow cleaning on the sample surface for 40 to 60 minutes before coating.

9. The method for preparing an anti-scouring coating structure of an aircraft engine blade disk according to claim 6, characterized in that: The number of the multiple alternating layers in step S2 is ≥3.

10. The method for preparing an anti-scouring coating structure of an aircraft engine blade disk according to claim 6, characterized in that: The clamp is a tubular structure, comprising a base and a mounting plate. The base is adapted to the diameter of the blade disk mounting shaft, and the mounting plate is fixedly connected to the base by bolts to fix the blade disk.

Citation Information

Patent Citations

  • Gradient multilayer composite coating structure with high erosion resistance and its preparation method

    CN107326361B

  • Novel water erosion resistant composite coating structure

    CN108754425A

  • Preparation method of anti-erosion and anti-fatigue integrated coating

    CN117344268A